Evaluating smart city technology efficiency and citizen satisfaction using data envelopment analysis - Bafail, Omer (International Journal of Strategic Property Management, 2025)
This study employs Data Envelopment Analysis (DEA) to evaluate the efficiency of the top 20 smart cities in converting Research and Development (R&D) investments into desired outcomes. Using national R&D expenditure (2015–2022) as input and ten criteria from the IMD 2024 Smart City Index report as outputs, the analysis reveals varying levels of efficiency among leading smart cities. Seven cities achieved perfect efficiency scores, while others, including some high-ranking cities, showed unexpected inefficiencies. This study provides valuable insights into resource utilization and identifies specific areas for improvement across structural and technological dimensions. The limitations include the focus on top-performing cities and the use of national R&D data as a proxy for city-specific investments. The findings of this study offer a foundation for policymakers and urban planners to optimize resource allocation and improve smart city initiatives, contributing to the ongoing development of sustainable urban environments in the face of technological advancements and urban challenges.